Community-based management of small reservoirs in an erosion-landslide-drought area in the dry tropical region of Kupang Regency - Punuf, Defritus Aldrin; Sartohadi, Junun; Setiawan, M Anggri (Journal of Degraded and Mining Lands Management, 2025)
A crucial component of water supply in arid tropical regions is the construction of small reservoirs. Interestingly, various problems arise in the construction and management of small reservoirs, so the role of small reservoirs in providing surface water is considered less than optimal. This study aimed to identify problems that cause the function of small reservoirs to be less than optimal and to provide direction for small reservoir management in dry tropical areas. The investigation was carried out in two primary stages: site analysis to identify issues with small reservoir usability and regional analysis to identify physical characteristics regionally. Determining small reservoir points was carried out using SPOT 6/7 imagery with a resolution of 1.5 m. Land system maps and morphometry were used to analyze the physical characteristics of the small reservoir site. Field surveys and in-depth interviews were conducted to identify the benefits and limiting factors in the construction of small reservoirs. The results revealed small reservoirs are found in locations with low altitudes (0-100 masl) and undulating terrain (8-15%). According to the findings, 95.3% of small reservoirs were still water-filled. However, many problems resulted in the suboptimal utilization of small reservoirs. Specifically, the problems faced were structural damage due to 1) erosion-landslides (74.77%),  2) sedimentation (33.64%), 3) seepage (7.48%), 4) embankment collapse (6.54%), and 5) leakage (2.80%). Most of the community does not utilize the small reservoirs due to the limited infrastructure. Pipes to distribute water are only available at around 46.73%, while water tanks are only 43.93%. Directions for future management are aimed at 1) adding infrastructure, 2) sediment management, and 3) community-based management.